The Community of Chlorophyta as Bioindicator of Water Pollution in Pandanduri Dam District of Terara East Lombok - Zikriah Zikriah; Imam Bachtiar; Lalu Japa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2020)
The Pandanduri Dam has a function as a support for agricultural irrigation water and also supports community activities so that it will affect the quality of its waters. The quality of the water needs to be analyzed because it can affect the aquatic ecosystem. This study aims to determine the level of water pollution in the Pandanduri Dam based on the phytoplankton community from the Chlorophyta Division. This type of research is descriptive exploratory. Sampling was carried out at 5 stations that were haphazardly selected with ecological representativeness consideration. Phytoplankton data were analyzed using the abundance formula, Shannon-Wiener diversity index, PIELOU uniformity index, and Simpson dominance index. The phytoplankton from the Chlorophyta Division found in the Pandanduri Dam were 14 species that areÃÂ Pediastrum duplexÃÂ var. Gracillimum, GoniumÃÂ sp. 1, GoniumÃÂ sp. 2, Coelastrum reticulatum, Scenedesmus acuminatus, CosmariumÃÂ sp., Chlamydomonas nasuta, ChlamydomonasÃÂ sp., Selenastrum capricornutum, Monoraphidium dybowskii, Monoraphidium contortum, Monoraphidium irregular, Westella botryoides, and Kirchneriella lunarisÃÂ consisting of 4 orders (Sphaeropleales, Chlorococcales, Chlamydomonadales and Desmidiales) and 10 genera (Pediastrum, Coelastrum, Scenedesmus, Gonium, Cosmarium, Chlamydomonas, Selenastrum, Monoraphidium, Westella, and Kirchneriella). The species diversity index of 2.21 is classified as moderate diversity, the species uniformity index is 0.83 which indicates even species growth, and the species dominance index indicates that no species dominates with a value of 0.12. The level of water pollution in the Pandanduri Dam was found in the moderate pollution category (oligotrophic).